Theory and problems of vector analysis and an introductin to tensor analysis - Spiegel, Murray R. (Singapore: McGraw-Hill International Book Company, 1981)
The guide to vector analysis that helps students study faster, learn better, and get top gradesMore than 40 million students have trusted Schaum's to help them study faster, learn better, and get top grades. Now Schaum's is better than ever-with a new look, a new format with hundreds of practice problems, and completely updated information to conform to the latest developments in every field of study.Fully compatible with your classroom text, Schaum's highlights all the important facts you need to know. Use Schaum's to shorten your study time-and get your best test scores!Schaum's Outlines-Problem Solved.